Implementing the Patient Activation Measure (PAM) in clinical settings for patients with chronic conditions: a scoping review. Issue 1 (12th July 2020) - Kearns, Rachael; Harris-Roxas, Ben; McDonald, Julie; Song, Hyun Jung; Dennis, Sarah; Harris, Mark
Abstract : Objective: The Patient Activation Measure (PAM) assesses the knowledge, skills and confidence of patients to manage their health, and has been consistently used as an outcome measure of health interventions. Using the PAM to tailor interventions to a patient's activation level is less understood. This literature review aimed to examine evidence for interventions using the PAM to tailor care for patients with chronic conditions, including enablers and barriers to implementation, and the impact on quality of care. Methods and analysis: A scoping review methodology was used to identify literature reporting on PAM-tailored interventions. The Insignia Health website and Medline database were searched. Included papers were published in English from 2004 to 2017, from Organisation for Economic Cooperation and Development countries, included adult patients with chronic conditions, and a PAM-tailored intervention. Eligible full-text papers were assessed against the inclusion criteria. Data were extracted into tables and summarised to assess the key findings, recurring themes and differences across papers. Results: Twenty-one papers describing the use of PAM-tailored interventions (n=21) were identified. Interventions included motivational interviewing, health coaching, self-management planning and risk profile assessment. The perceived value and function of the PAM held by organisations, clinicians and patients influenced implementation and use. Evidence for the impact of PAM-tailored interventions on quality of care was limited. Conclusion: The PAM is being used to tailor a range of interventions for patients with chronic conditions. Clinician perceptions and understanding about the PAM's value and purpose influenced implementation. Further research is needed about how PAM-tailored interventions can be integrated into clinical practice, and guide the patient-clinician interaction, in ways that improve the quality of patient care.